Promoting democratic participation in a small municipality through university extension as a process of inclusion and citizen education (Research, Society and Development, 2019)
The study aims to analyze a Participatory Budgeting experience in the city of Currais Novos - RN. Regarding the methodology were applied questionnaires and rounds of conversation, local plenary meetings in six communities / neighborhoods and a General Plenary. As a result it was found that the deficiencies pointed out by the localities participating in this process refer to the need for investments by the Municipal Government in basic actions related to works and services in infrastructure, safety, health and education, which currently stand as the biggest problems in the world. municipal locus. Finally, the study concludes that the small amount of resources earmarked for the action, implied in severe fragmentation of the attendance to the needs of the population and that the process needs more effective support regarding the monitoring and budgetary analysis of its current actions.